Analyzing the Impact of Human Element and Human Error on Seafarer Performance, Mediated by Safety Culture: Case study Indonesian Seafarer - ., Moejiono; Jinca, M Yamin; Gunawan, Aang; Barata, Fausta Ari (Journal of Cultural Analysis and Social Change, 2025)
This study aims to analyze how the Human Element, as recognized by the International Maritime Organization (IMO), along with human error and safety culture, influences the performance of Indonesian maritime officers. Employing a quantitative approach with the Structural Equation Modeling (SEM) method via SmartPLS 4, this causal study involved 243 Indonesian seafarers with a minimum of two years of experience, selected through purposive sampling. The research findings indicate that both the measurement and structural models possess excellent validity and reliability. Indicators demonstrate outer loading values above 0.816, Average Variance Extracted (AVE) above 0.669, and Composite Reliability (CR) above 0.919, signifying the robust quality of the measurement model. Furthermore, the Human Element and Human Error explain 61% of the variance in Safety Culture, while the combination of variables accounts for 78% of the variance in Seafarer Performance, with a Standardized Root Mean Square Residual (SRMR) of 0.067 indicating a good model fit. This research makes a significant contribution by addressing previous study gaps that focused on the quantity of seafarers, shifting instead to the qualitative aspects of the Human Element and its impact on officer performance. Consequently, these findings can be implemented by the shipping industry to enhance safety and improve seafarer performance.